2022
DOI: 10.1002/adfm.202204622
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Guided Fast and Oriented Assembly of MXene into Scalable Pristine Hydrogels for Customized Energy Storage and Water Evaporation Applications

Abstract: The assembly of MXene nanosheets into a hydrogel framework is key to their grand success in practical applications. However, the scalable realization of such stable structures is challenging and requires critically high dispersion concentration for gelation. Herein, a simple yet highly controllable approach for the development of 2D and 3D monolithic hydrogels of MXene via electro‐tunable ordered assembly is reported. Directional electrophoretic drag of MXene and their gelation by voltage‐controlled in situ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The significantly improved specific capacitance and the rate performance of the HMH3 electrode in comparison to MH clearly indicate the importance of the holey-MXene networks in the hydrogel structure. Figure d compares the specific capacitance and rate performance of the HMH3 electrode at 1000 mV s –1 with other reported MXene-based electrodes. ,, It is evident that the specific capacitance of HMH3 at 1000 mV s –1 with a capacitance retention of 94.4% is one of the best electrodes ever reported so far and surpasses the performance of most of the state-of-art MXene-based electrodes (Table S3).…”
Section: Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The significantly improved specific capacitance and the rate performance of the HMH3 electrode in comparison to MH clearly indicate the importance of the holey-MXene networks in the hydrogel structure. Figure d compares the specific capacitance and rate performance of the HMH3 electrode at 1000 mV s –1 with other reported MXene-based electrodes. ,, It is evident that the specific capacitance of HMH3 at 1000 mV s –1 with a capacitance retention of 94.4% is one of the best electrodes ever reported so far and surpasses the performance of most of the state-of-art MXene-based electrodes (Table S3).…”
Section: Results and Discussionmentioning
confidence: 89%
“…The values of the specific capacitances of HMH3 with superb rate performances are not only higher than MH but also surpass the performance of other MXene based symmetric capacitors reported so far. 55 , 63 65 Besides, in this symmetric cell setup, the HMH3 electrode can retain 75% of its capacitance with a Coulombic efficiency of 95% for over 10,000 charge–discharge cycles at a high current density of 12.5 A g –1 ( Figure S24 ). These results illustrate that the HMH3 electrode retains its excellent performance in the symmetric configuration, highlighting its potential for practical applications.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Furthermore, the solar water evaporation rate of the biomimetic PDMX/HPP aerogel is compared with those of some previously reported materials (Figure 4f, Table S2, Supporting Information). [56][57][58][59][60][61][62][63][64][65][66][67][68] One can see that the solar water evaporation rate of the biomimetic PDMX/HPP aerogel is higher than those of some previously reported materials. In addition, the collection of condensed clean water can reach 4.33 kg m −2 for 4 h under one sun illumination.…”
Section: Resultsmentioning
confidence: 99%
“…13 Thus, researchers reported that adding organic solvents to the hydrogels can play a role in antifreezing. [14][15][16][17] Researchers also reported that a mixture of glycerol and water have freezing points lower than À40 C, whereas pure glycerol has freezing points of only À13 C. Because water and glycerol has a lot of hydrogen bonds that will destroy ice lattice formation. 18 At the same time, the hydrogen bond between water and glycerol prevents the evaporation of water.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yu and colleagues reported an antifreezing organic hydrogel with CaCl 2 /sorbitol solution as the medium, it has good tensile properties and does not deform at low temperatures 13 . Thus, researchers reported that adding organic solvents to the hydrogels can play a role in antifreezing 14–17 . Researchers also reported that a mixture of glycerol and water have freezing points lower than −40°C, whereas pure glycerol has freezing points of only −13°C.…”
Section: Introductionmentioning
confidence: 99%